Secondary school students' perceptions of scientific and religious positions on miracles - Billingsley, Berry (Science & Christian belief, 2021)
This paper reports on a study designed to discover how students characterise the scientific and religious positions on miracles and their access to a range of views on how science and religion relate. The study is part of a larger research initiative exploring the value of scholarly reasoning about the interactions between science and religion as a resource for educators, researchers and others seeking ways to advance young people's epistemic insight. Teaching epistemic insight, 'knowledge about knowledge', includes considering the power and limitations of science in the context of different types of questions and how science relates to other ways of knowing. For many decades in schools in England and internationally the accepted practice has been to teach lessons about the nature of science within the confines of a subject (science) that focuses on teaching scientific content. This means that students' opportunities for learning about science as a discipline in school can be limited to studying questions that are very amenable to science. The paper draws on the findings from a survey of 2,530 students and interviews with 61 students aged 14-19 to discuss the extent to which students seem to be accessing an appreciation of the power, relevance and limitations of science. The paper then examines some possible consequences of the findings and makes recommendations for science communication and secondary school education.